(untitled) (Annals of Medical Research, 2022)
Aim: The c-Jun NH2-terminal kinases (JNK) signaling pathway is an important signaling pathway in liver regeneration. it was planned to investigate the expression levels of Mitogen Activated Protein Kinase Kinase (MKK)-4 and -7 (MKK7), which are mediator molecules involved in the JNK signaling pathway and Activating Transcription Factor (ATF) 2 transcription factor genes, which are in the last stage of the signaling pathway, in liver tissues in young and old mice. In addition, it was aimed to examine the ultrastructural changes caused by aging in hepatocytes. Material and Methods: We examined MKK4, MKK7 and ATF2 expression levels by using Real Time Polymerase Chain Reaction (RT-qPCR) method. Transmission electron microscopy (TEM) was used to observe the ultrastructural changes of hepatocytes. Results: While MKK4 and ATF2 gene expressions reduced in the liver of aged mice, MKK7 gene expression did not change. In TEM examinations, granular endoplasmic reticulum loss and mitochondrial damage were observed in elderly individuals. Conclusion: According to these results, spontaneous liver damage that can be seen in aged subjects may be caused by disruption in cellular signaling pathways and organelle damage in hepatocytes.